Coordination of Energy Storage and Wind Power Plant considering Energy and Reserve Market for a Resilience Smart Grid. (August 2020) - Choopani, Keyvan; Effatnejad, Reza; Hedayati, Mahdi
Highlights: The proposed scheme is a Mixed-Integer Nonlinear Programming (MINLP) problem. the scheduling planning of wind and pumped storage is stochastic problem scheduling which is named stochastic Security-Constrained Unit Commitment (SCUC) Summary: The intermittency of wind power generation causes some challenges in scheduling normal operation and emergency states. The presence of Pumped Storage (PS) power plants along with wind power plants can neutralize the negative impacts of varying production. It can also improve the resilience performance of the power system. The main components of this paper are to investigate the effect of coordination between wind and PS power plants and to consider the energy market and reserve on normal operation and emergency (resilience) of the power system. Since the output power of wind generation is intermittent, the scheduling of wind and PS is stochastic problem scheduling which is named stochastic Security-Constrained Unit Commitment (SCUC). The uncertainty of wind power generation and load are modeled by the Monte Carlo simulation method. Non-convexity and nonlinearity are two important points that prevent the global optimal solution to the problem. The proposed scheme is a Mixed-Integer Nonlinear Programming (MINLP) problem. The proposed model by Lagrange relaxation will become a Mixed-Integer Linear Programming (MILP) problem. One important factor that problem makes nonconvex is nonexistence affine state of equality constraints. Since AC load flow constraints make the problem a complex non-convex and non-linear problem. Because convexity and faster solving (the system should restore very quickly in an event.) is used DC load flow. Therefore, the optimal solution is guaranteed in this article. The obtained results demonstrate the effectiveness of the proposed method in normal and resiliency operation.